Lacrimal Cytokines Assessment in Subjects Exposed to Different Levels of Ambient Air Pollution in a Large Metropolitan Area - Matsuda, Monique; Bonatti, Rodolfo; Marquezini, Mônica V.; Garcia, Maria L. B.; Santos, Ubiratan P.; Braga, Alfésio L. F.; Alves, Milton R.; Saldiva, Paulo H. N.; Monteiro, Mário L. R. (PloS one, 2015)
Air pollution is one of the most environmental health concerns in the world and has serious impact on human health, particularly in the mucous membranes of the respiratory tract and eyes. However, ocular hazardous effects to air pollutants are scarcely found in the literature. Panel study to evaluate the effect of different levels of ambient air pollution on lacrimal film cytokine levels of outdoor workers from a large metropolitan area. Thirty healthy male workers, among them nineteen professionals who work on streets (taxi drivers and traffic controllers, high pollutants exposure, Group 1) and eleven workers of a Forest Institute (Group 2, lower pollutants exposure compared to group 1) were evaluated twice, 15 days apart. Exposure to ambient PM2.5 (particulate matter equal or smaller than 2.5 μm) was 24 hour individually collected and the collection of tears was performed to measure interleukins (IL) 2, 4, 5 and 10 and interferon gamma (IFN-γ) levels. Data from both groups were compared using Student's t test or Mann- Whitney test for cytokines. Individual PM2.5 levels were categorized in tertiles (lower, middle and upper) and compared using one-way ANOVA. Relationship between PM2.5 and cytokine levels was evaluated using generalized estimating equations (GEE). PM2.5 levels in the three categories differed significantly (lower: ≤22 μg/m3; middle: 23-37.5 μg/m3; upper: >37.5 μg/m3; p<0.001). The subjects from the two groups were distributed unevenly in the lower category (Group 1 = 8%; Group 2 = 92%), the middle category (Group 1 = 89%; Group 2 = 11%) and the upper category (Group 1 = 100%). A significant relationship was found between IL-5 and IL-10 and PM2.5 levels of the group 1, with an average decrease of 1.65 pg/mL of IL-5 level and of 0.78 pg/mL of IL-10 level in tear samples for each increment of 50 μg/m3 of PM2.5 (p = 0.01 and p = 0.003, respectively). High levels of PM2.5 exposure is associated with decrease of IL-5 and IL-10 levels suggesting a possible modulatory action of ambient air pollution on ocular surface immune response.